ASAS PROPORSIONALITAS SEBAGAI LANDASAN PERTUKARAN HAK DAN KEWAJIBAN PARA PIHAK DALAM KONTRAK KOMERSIAL - Agus Yudha Hernoko (Jurnal Hukum dan Peradilan, 2016)
In commercial contracts, the debates about 'fairness and balance' that led to the 'injustice and imbalance' position of the parties basically irrelevant to be disclosed. It is based on the consideration that the positions of the parties in commercial contracts is similar on the stage of the negotiation process (pre-contractual phase), the formation of the contract (contractual phase) and the execution of the contract (post-contractual phase). Meanwhile, the results of the exchange of the interests of the parties considered fair if it lasts proportionally. The proportionality of exchange of rights and obligations under commercial contracts do not demand results that are always balanced and same (equilibrium-mathematically), therefore the differences in the results are considered fair and reasonably acceptable if the exchange process of the rights and obligations stay proportional. Application of the principle of proportionality in the whole chain of contractual process is basically a manifestation of the doctrine of "fairness of contract" adopted and developed today.Keywords : the exchange of rights and obligations, the principle of proportionality,fairness doctrine in a contract